OPTIMUM EVALUATION OF HARMONIOUS COMPONENTS OF NON-STATIONARY TRAFFIC - Ладигіна, Ольга Анатоліївна (Science-based technologies, 2019)
The purpose of the work is experimental confirmation of the method for optimal estimation of harmonic components of non-stationary traffic in a given frequency range. That is, the essence of optimal estimation is to determine the optimal estimate of the true value of the traffic from the distorted interference of the traffic realization. If there is a harmonious spectrum, then it is periodic and repeated application of the Fourier transform detects peaks that repeat with a certain period. Therefore, it is advisable to assume that such an implementation of traffic is observed that has a length of at least two, three periods, which allows optimal estimation of its parameters. The statistical problems of optimal estimation of signal parameters against a background of interference are solved using the maximum likelihood criterion under the assumption that the estimates must have a Gaussian distribution. If we consider this assumption as a first approximation, then we can choose the least squares criterion as an optimality criterion. To solve the equations of frequency and phase optimization, a numerical graph-analytical iterative method has been developed that allows one to obtain optimal estimates of the frequency and phase with a predetermined accuracy, as well as the errors of these estimates expressed in terms of the relative length of the interval estimates and residuals of the optimization equations. The task of spectral analysis of a periodic signal was generalized to the case of interference at different signal-to-noise values, which made it possible to verify the harmonic components of periodic traffic against the background of interference and to estimate the parameters of the main harmonic of the traffic (amplitude, frequency, and phase) by the least-square method based on monitoring results traffic envelope over several periods. This method in the future may allow us to study the effect of all parameters in the full amount of interference on the maximum amount of information that a signal transmits. The created calculation package for determining the optimal estimates of the harmonic components of periodic traffic allows performing various large-scale experiments to study periodic traffic based on the results of field observations of unsteady traffic in heterogeneous computer networks